DEVELOPMENT OF INFORMATION SYSTEM FOR MONITORING PREGNANCY HEALTH AND NUTRITION ADEQUACY OF TODDLERS FOR STUNTING PREVENTION - Hidayah, Lailatul; Setio Pambudi, Doni; Syauqi Mubarok, Muhammad; Ngatini, Ngatini (Jurnal Pilar Nusa Mandiri, 2021)
Abstract—Stunting is a health problem caused by a lack of nutritional intake for a long time, resulting in impaired growth in children. Stunting has become one of the government's priorities due to the large number of stunting incidents in Indonesia. The lack of knowledge of mothers about nutrition and good parenting is one of the causes of stunting. Intensive provision of information and health monitoring of pregnant women from time to time will reduce the incidence of stunting in toddlers. The purpose of this research is to develop an information system that can contain various information on pregnancy health and parenting to avoid stunting and can send it regularly to user according to their needs. This information system development adapts the Prototyping model of the Software Development Life Cycle method. The result of this study is an information system that will help disseminate various information on how to fulfill proper nutrition in pregnant and lactating mothers. In addition, the system will send messages via email and Short Message Service (SMS) which will serve as reminders for patients. This information system also functions as a toddler or pregnancy health monitoring tool based on the data entered into the system. This study result tackle one of the causes of stunting, namely the lack of information on maternal health and good parenting. Researchers hope that this solution can contribute to help the government to realize its vision of reducing stunting rates in Indonesia. Abstrak— Stunting merupakan masalah kesehatan yang disebabkan oleh kurangnya asupan gizi dalam waktu yang cukup lama sehingga mengakibatkan gangguan pertumbuhan pada anak. Stunting telah menjadi salah satu prioritas pemerintah karena banyaknya jumlah kejadian stunting di Indonesia. Minimnya pengetahuan ibu mengenai pemberian gizi dan pola asuh yang baik menjadi salah satu penyebab terjadinya stunting. Pemberian informasi secara intensif dan monitoring terhadap ibu hamil dari waktu ke waktu akan mengurangi terjadinya stunting pada balita. Tujuan dari penelitian ini adalah mengembangkan sebuah sistem informasi yang dapat memuat berbagai informasi kesehatan kehamilan dan pola asuh agar terhindar dari stunting dan dapat mengirimkannya secara berkala pada pengguna sesuai kebutuhannya. Pengembangan sistem informasi ini mengadaptasi metode pengembangan perangkat lunak model Prototyping. Hasil dari penelitian ini berupa Sistem Informasi yang akan membantu untuk melakukan diseminasi berbagai informasi mengenai cara pemenuhan gizi yang baik dan benar pada ibu hamil dan menyusui. Selain itu, sistem akan mengirimkan pesan melalui surel dan Short Message Service (SMS) yang akan menjadi pengingat bagi pasien. Sistem Informasi ini juga berfungsi sebagai alat monitoring kesehatan balita atau kehamilan berdasarkan data yang dimasukkan ke dalam sistem. Solusi ini merupakan wujud penanggulangan salah satu penyebab stunting yaitu minimnya informasi kesehatan ibu mengenai pola pengasuhan yang baik. Peneliti berharap solusi ini dapat berkontribusi untuk mempermudah pemerintah dalam mewujudkan visinya untuk mengurangi tingkat stunting di Indonesia.